The Dynamics of Coal Mining RKAB Adjustment by Kementerian ESDM: Balancing Production Control and Labor Risk in the Mining Sector of Kalimantan Timur - Muhammad Hasbi Mo’a W.A; Afni Nurvita Damayanti Wijaya; Jauchar B (Jurnal Kajian dan Penelitian Umum, 2026)
This study analyzes the dynamics of adjustments to the Work Plan and Budget Cost (Rencana Kerja dan Anggaran Biaya, RKAB) for coal mining by the Kementerian Energi dan Sumber Daya Mineral and their implications for mining labor risks in East Kalimantan. Employing qualitative, juridical-normative, and public policy analysis approaches, this study examines RKAB regulations, government performance reports, official statistical data, and relevant scholarly literature on energy transition and employment. The findings indicate that RKAB adjustments have legitimacy as an instrument of production control, particularly in reducing oversupply, maintaining price stability, and securing national coal reserves. However, in regions whose economies remain dependent on mining, such as East Kalimantan, this policy has the potential to generate risks for direct workers, contractor workers, and mining-supporting sectors. This study underscores the need to integrate production control, labor protection, reskilling, tripartite dialogue, and regional economic diversification to ensure that RKAB adjustments are implemented in a more equitable and sustainable manner within the context of coal-producing regions that are vulnerable to changes in production levels and local labor markets.